Monetary policy, central bank information, and bank lending: Evidence from German banks - Sophia List; Norbert Metiu (Deutsche Bundesbank, 2025)
This paper examines the impact of monetary policy and central bank information on banks' lending using data on German bank balance sheets from 2002 to 2018. Local projection estimates show that the volume of loans to non-financial corporations declines significantly after a restrictive monetary policy shock that is independent of non-monetary information in central bank announcements. This decline is stronger for relatively small banks with less liquid balance sheets, which have less access to external financing. By contrast, the volume of loans increases significantly following an unexpected monetary policy rate tightening that is associated with favorable information on the economic outlook. This increase is stronger for relatively small banks with more liquid balance sheets, which are better able to boost lending. This insight adds a new dimension to the role of banks in the transmission of central bank policy.
Keywords: C33; E51; E58; G21; 330; Bank lending; Central bank; Credit; Information shock; Monetary policy; Transmission mechanism